Application Of Oil Palm Empty Fruit Bunch (Opefb) – Treated Palm Oil Mill Effluent (Pome) Sludge Pellet On Soil Erosion And Its Implication On Simulated Experiment - Khalaf Ali, Almanasir Yazan (2021)
Palm Oil Mill Effluent (POME) sludge and Oil Palm Empty Fruit Bunches (OPEFB) are two major by-products of lignocellulosic biomass and now become a major disposal problem. Fundamentally, recycle is one of the waste management hierarchy. Given the fact that potential utilization of both by-products in soil management within the watershed, hence, it warrants further investigation on possible implications of the water quality of the adjacent water bodies. This study has three objectives; (1) To determine the water absorption and thickness swelling behaviours of the OPEFB-POME pellets. (2) To evaluate the effectiveness of plot OPEFB- POME pellets application for soil erosion mitigation. (3) To investigate the effect of the plot OPEFB-POME pellets application on the water quality. Hence, the focus will be on the effectiveness of blended treated POME sludge and OPEFB pellets as biodegradable soil cover using rainfall simulator with different amount of pellets applied in the specific plot, 0 g/ ft2, (T1), 154 g/ ft2, (T2), 310 g/ ft2, (T3), 465 g/ ft2 (T4), and 620 g/ ft2, (T5). These experiments followed by water quality assessment, where dissolved oxygen (DO), salinity, temperature, turbidity, pH, electrical conductivity (EC), total dissolved solids (TDS) chemical oxygen demand (COD) and phosphorus (P) are analysed. Statistical analysis i.e., ANOVA one-way and Principle Component Analysis (PCA) were used to provide quantitative analysis of this study. Note, water absorption and thickness swelling of the pellets are measured according to ASTM D-1037-99 prior to rainfall simulator testing. It is suggested that pellets-II (OPEFB-POME 40:60 ratio) has a better dimensional stability.